2019
DOI: 10.1136/oemed-2019-106175
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to dust and to fumes, work as a welder and invasive pneumococcal disease risk

Abstract: ObjectivesOccupational exposures to metal fumes have been associated with increased pneumonia risk, but the risk of invasive pneumococcal disease (IPD) has not been characterised previously.MethodsWe studied 4438 cases aged 20–65 from a Swedish registry of invasive infection caused by Streptococcus pneumoniae. The case index date was the date the infection was diagnosed. Six controls for each case, matched for gender, age and region of residency, were selected from the Swedish population registry. Each control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 25 publications
0
40
0
Order By: Relevance
“…Other studies have, however, found that certain kinds of occupational exposures increase the risk of pneumonia [57].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Other studies have, however, found that certain kinds of occupational exposures increase the risk of pneumonia [57].…”
Section: Discussionmentioning
confidence: 94%
“…No significant association between occupational exposure divided into agents with different molecular weights and respiratory tract infections or use of antibiotics was found in the previous studies. Other studies have, however, found that certain kinds of occupational exposures increase the risk of pneumonia [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Occupational exposure to welding fumes, silica dust 5 The mapping of studies per world region was as follows: Europe And Central Asia (n=75), East Asia and Pacific (n=67), North America (n=38), sub-Saharan Africa (n=33), Latin America and Caribbean (n=28), Middle East and North Africa (n=18) and South Asia (n=11). Thus, most studies were administered in Europe and Central Asia (27.8%), followed by East Asia and Pacific (24.8%), North America (14.1%) and sub-Saharan Africa (12.2%) (https:// ourworldindata.…”
Section: Streptococcus Pneumoniaementioning
confidence: 99%
“…Several epidemiological studies have shown an increased frequency of pneumonia among welders. Welding fumes have also been associated with invasive pneumococcal disease (16). Exposure estimates associated with asthma and pneumonia are lacking.…”
Section: Brief Summary Of Health Effectsmentioning
confidence: 99%